Determination of Educational Success: Systems Thinking, Empowerment, Self Potential - Kholdun, Ibnu; Ali, Hapzi; Anwar Us, Kasful (International Journal of Advanced Multidisciplinary, 2023)
This article analyzes the factors that influence the exploration of external potential and empowerment for educational success, so that the education of a student in an institution or company is able to place him/her as competent and professional human resources. The method of writing this Literature Review article is the library research method, sourced from online media such as Google Scholar, Mendeley and/or other academic online media.The results of this article are that: Determination of Educational Success 1) System Thinking, 2) Empowerment 3) Self Potential, apart from the above determination there are also other factors such as social background , culture and learning process.